Closing Gender Gaps in India : Does Increasing Womens' Access to Finance Help? - Khera, Purva (IMF Working Papers; Working Paper ;, 2018)
Gender gaps in womens' economic opportunities-labor market and entrepreneurship-have remained high in India. Lack of adequate collateral limits women entrepreneurs' ability to access formal finance, leaving them to rely on informal sources, constraining their growth. A small-open economy DSGE model is built to investigate the long-run macroeconomic impacts from closing gender gaps in financial access. Results suggest that an increase in women entrepreneurs access to formal credit results in higher female entrepreneurship and employment, which boosts India's output by 1.6 percent. However, regulations and gender-specific constraints in the labor market limit potential gains as females' access to quality jobs in the formal sector remains restricted. The paper shows that the factors influencing the number of females are different from those influencing the share of females in formal economic activity. Combining gender-targeted financial inclusion policies with policies that lower constraints on formal sector employment could boost India's output by 6.8 percent.